Pilot Data for Study of Gender & the Adoption of Agricultural Technologies in Cassava Cultivation - Ng'ang'a, A.; Trachtman, Carly; Ligon, Ethan (International Food Policy Research Institute, 2022)
These are data for a pilot study conducted in Kenya which was meant to expose differences in the rates at which female and farmers adopted improved cassava cultivars, and whether these differences responded to different forms of engagement via extension activities.